PENGARUH MOTIVASI, KOMPENSASI SERTA LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI DINAS PERTANIAN DAN KETAHANAN PANGAN - Nawaksara Winangun, Ngurah Manik; Surya, Ida Bagus Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p09, 2024)
Spirit At Work is the ability of a person or group to work diligently in pursuit of a common goal, so that work can be completed more quickly and get satisfactory results. If morale is low, the possibility of participation will be limited to what was ordered. On the other hand, the presence of high Spirit At Work reflects that individuals will participate enthusiastically with full commitment. Employee morale is shown through employee work patterns in completing their duties and responsibilities. This research was conducted at the Department of Agriculture and Food Security, Bali Province. The number of samples used were 163 employees of the Department of Agriculture and Food Security of the Province of Bali, The purpose of this study was to analyze the effect of work motivation, compensation, and work environment on Spirit At Work. with the  method determining the sample is Quota Sampling. Data was analyzed using Multiple Linear Regression analysis techniques. The results of this study indicate of work motivation, compensation, and work environment have a positive and significant effect on the morale of the employees of the Department of Agriculture and Food Security in the Province of Bali.